Minat Beli Konsumen Atas Produk Sepeda Motor Yamaha MIO M3 - Anggara, Kurnia Yudha; Astuti, Miguna; Aryani, Lina (LPPM Institut Bisnis dan Informatika Kesatuan, 2020)
This research is a quantitative research that aims to determine the effect of price, Brand Image and Quality Product. The population to consumers who come to Yamaha dealers in the area of South Jakarta City, the sample size was taken as many as 75 respondents, with probability sampling method, especially Random Sampling. Data collection is done through the distribution of questionaires. The analysis technique used is the method of PLS (Partial Last Square) analysis. The results of this study indicate that (p1) price has significant effect on buying interest. Keywords: Price, Brand Image, Product Quality, and Purchase Interest